Target behaviors in educational social skills programs for parents - Margarette Matesco Rocha; Priscila Andrade; Thiago Leão Siveira Dourado (Universidade Federal de Santa Maria (UFSM), 2011)
This article presents a review of Educational Social Skills (THSE) training programs offered to parents, highlighting the behaviors that were the focus of intervention. The research was performed in electronic databases (Scielo, Pepsic and Lilacs) and the bank of thesis and dissertations of Federal University of São Carlos(UFSCar). Five studies were selected and the results discussed considering the importance of the trained skills for parent-children interaction. It was considered that although there are different models of programs, there are recurence in the selection of some educational social skills, showing that they may be relevant for the parent-children interaction